Identification of sources of resistance in geographically diverse wheat accessions to stripe rust pathogen in China. (August 2019) - Mu, Jingmei; Wang, Qilin; Wu, Jianhui; Zeng, Qingdong; Huang, Shuo; Liu, Shengjie; Yu, Shizhou; Kang, Zhensheng; Han, Dejun
Abstract: Stripe rust, caused by Puccinia striiformis f. sp. tritici, is one of the most damaging diseases of wheat in the world. China is one of the most important regions of wheat production and stripe rust epidemics. The spread of Yr26 -virulent races V26 has threatened wheat production in China. It is urgent to identify new resistance sources for use in breeding programs. A total of 60 accessions from different wheat regions in the world, showing excellent field resistance in previous study were examined in more details at Yangling under artificially inoculation conditions and Tianshui under naturally infection from 2015 to 2017. Seedling tests were also conducted using two Yr26 -virulent races and eight Yr26 -avirulent races. The combined field and seedling response data and pedigrees of the 60 entries were used to postulate the resistance genes involved. Molecular markers that are linked to some previously reported stripe rust resistance genes were used to validate the postulated genes. Resistance genes in 4 accessions that were resistant in all race tests in the seedling stage and field tests could not be predicted. These 4 accessions with all stage resistance should combine with other Yr genes to obtain durable resistance. Resistance in 24 accessions was attributed, at least in part, to combinations of known genes. Fifty accessions were susceptible to the Yr26 -virulent races in the seedling stage, but resistant in the fields of both locations. With at least partial assurance, the genes for effective resistance in the 50 accessions are different from those already widely used in Chinese wheat varieties. Therefore, these 50 accessions should be used in breeding programs to developing new cultivars with effective resistance to the new emerging races and other predominant races. Highlights: Resistance genes in 4 accessions that were resistant in all Pst race tests in the seedling stage and field tests could not be predicted. Resistance in 24 accessions was attributed, at least in part, to combinations of known genes. Resistance genes in the 50 accessions with adult plant resistance are different from those already widely used in Chinese wheat varieties.